Hugo and Russells pharmaceutical microbiology - Brendan F Gilmore; Denyer, Stephen P (New Delhi Wiley, 2024)
Hugo and Russell's Pharmaceutical Microbiology has long served as the sole comprehensive textbook covering the subject. The ninth edition of this textbook has been updated to a critical new period in the advancement of medical and pharmaceutical research and development. Its experienced editors have incorporated contributions from subject experts and created a text which will serve the next generation of pharmacy students, pharmaceutical industry scientists and researchers. Material covering the fundamentals of microbiology, microbial behaviour, laboratory investigation, microbe-host interactions, antibiotic resistance, emerging pathogens, public health microbiology, healthcare-associated infection and pharmaceutical product manufacture.
Keywords: Pharmacology